A 14-year follow-up study of localized juvenile periodontitis treated by scaling and root planing, systemic metronidazole, and subgingival curettage: a case report. - (:unkn) unknown (My University, 1996)
This 14-year longitudinal case study involved the treatment of localized juvenile periodontitis in a male patient commencing at 15 years of age, by scaling and root planing, systemic metronidazole, and subgingival curettage along with supervised maintenance. No other surgery was required. All symptoms disappeared by the end of the active treatment phase, and radiographic evaluation and reduced probing pocket depth measurements showed adequate bone fill to have occurred and be preserved over this period.